A tale of two countries: comparing civic education in the Philippines and Singapore. Issue 1 (2nd January 2016) - Baildon, Mark; Sim, Jasmine B.-Y.; Paculdar, Agnes
Abstract : This article provides a comparative analysis of citizenship education in the Philippines and Singapore. Through an analysis of historical contexts, citizenship education policy and curriculum, it examines Makabayan in the Philippines and National Education in Singapore. It identifies particular policy and curriculum trajectories as responses to national and global imperatives to demonstrate how countries are redefining the kinds of knowledge, skills and values deemed necessary for national citizenship in global contexts. This comparative case study illustrates some of the tensions and contradictions facing citizenship education in new global contexts and highlights the different ways countries try to manage these tensions through citizenship education policies and curricula. Findings point to different factors that shape and constrain the implementation of citizenship education programmes in both countries.